THE INFLUENCE OF WORK DISCIPLINE AND WORK MOTIVATION ON THE PERFORMANCE OF PT EMPLOYEES. INDONESIAN RAILWAYS (PERSERO) DIVRE III PALEMBANG - Primasari Fitria; Amidi Amidi; Yunita Febriani; Desti Azahra Kurnia (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
This research aims to determine the influence of work discipline and wprk motivation on the performance of PT. Indonesia Railways (Persero) Divre III Palembang. The type of research used is associative research. The data collection technique in this research is by distributing questionnaires. The population wa 59 respondents. The analiysis used this research is multiple Linear regression analysis, with a significance level of 10%. The research results ahow that. 1) Three is a positive and signitificant influence of work discipline and work motivation on employee performance at PT. Indonesian Railways (Persero) Divre III Palembang. 2) There is a positive and signitificant influence of work discipline on employe performance at PT. Indonesian Railways (Persero) Divre III Palembang. 3) There is a positive and signitificant influence of work motivation on employee performance at PT. Indonesian Railways (Persero) Divre III Palembang